2022
DOI: 10.3389/fmicb.2022.920052
|View full text |Cite
|
Sign up to set email alerts
|

Alcaligenes ammonioxydans HO-1 antagonizes Bacillus velezensis via hydroxylamine-triggered population response

Abstract: Antagonism is a common behavior seen between microbes in nature. Alcaligenes ammonioxydans HO-1 converts ammonia to nitrogen under aerobic conditions, which leads to the accumulation of extracellular hydroxylamine (HA), providing pronounced growth advantages against many bacterial genera, including Bacillus velezensis V4. In contrast, a mutant variant of A. ammonioxydans, strain 2-29, that cannot produce HA fails to antagonize other bacteria. In this article, we demonstrate that cell-free supernatants derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…71 . Later, NH 2 OH production by A. faecalis was also shown to have antifungal 72,73 and antibacterial 74,75 effects. NH 2 OH secretion could, therefore, be a competitive strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…71 . Later, NH 2 OH production by A. faecalis was also shown to have antifungal 72,73 and antibacterial 74,75 effects. NH 2 OH secretion could, therefore, be a competitive strategy.…”
Section: Discussionmentioning
confidence: 99%
“…NH 2 OH secretion could, therefore, be a competitive strategy. In fact, A. faecalis grown in de ned co-cultures had a competitive advantage over its concomitant organisms, which the authors ascribed to the production of NH 2 OH 75 . Furthermore, A.…”
Section: Discussionmentioning
confidence: 99%
“…First, the biochemistry of transforming ammonia into NH 2 OH during the Dirammox process remains a mystery and requires further investigation. From a bioenergetics perspective, it is unclear whether the ammonia oxidation process provides extra energy for bacterial growth or serves as a detoxification mechanism, while the accumulation of extracellular hydroxylamine by the genus Alcaligenes provided pronounced growth advantages compared to other bacteria . Additionally, the extent to which the Dirammox process contributes to the global nitrogen balance is unclear.…”
mentioning
confidence: 99%
“…From a bioenergetics perspective, it is unclear whether the ammonia oxidation process provides extra energy for bacterial growth or serves as a detoxification mechanism, while the accumulation of extracellular hydroxylamine by the genus Alcaligenes provided pronounced growth advantages compared to other bacteria. 11 Additionally, the extent to which the Dirammox process contributes to the global nitrogen balance is unclear. It is necessary to apply 15 N tracing experiments to accurately quantify a variety of simultaneously occurring gross nitrogen transformation processes, including Dirammox in actual environments.…”
mentioning
confidence: 99%
“…In this work, we discovered a redistribution phenomenon for nitrogen between the Dirammox and cell growth processes. A. ammonioxydans HO-1 chose the Dirammox process instead of the physiological state with a rapid doubling time and higher biomass during the course of evolution.Recent studies have shown that A. ammonioxydans HO-1 exhibits a pronounced antagonism activity against a wide range of microbes like B. velezensis V4 through the production of extracellular NH 2 OH, a key intermediate of the Dirammox(Gao et al, 2022). Meanwhile, the products of Dirammox, NH 2 OH, could degrade antibiotics(Su et al, 2023) and chemically transform organic micropollutants(Su et al, 2021) to increase bacterial tolerance in complex natural environments.…”
mentioning
confidence: 99%